Strongly oxidizing perylene-3, 4-dicarboximides for use in water oxidation photoelectrochemical cells. Issue 8 (4th September 2015) - Lindquist, Rebecca J.; Phelan, Brian T.; Reynal, Anna; Margulies, Eric A.; Shoer, Leah E.; Durrant, James R.; Wasielewski, Michael R.
Abstract : Perylene-3, 4-dicarboximide (PMI) based chromophores are explored for use in photoelectrochemical cells (PECs) for solar fuels generation. Abstract : Perylene-3, 4-dicarboximide (PMI) based chromophores have demonstrated the ability to inject electrons into TiO2 for dye-sensitized solar cell applications and to accept electrons from metal complexes relevant to water oxidation, but they are nearly unexplored for use in photoelectrochemical cells (PECs) for solar fuels generation. A series of related PMIs with high oxidation potentials and carboxylate binding groups was synthesized and investigated for this purpose. Charge injection and recombination dynamics were measured using transient absorption (TA) spectroscopy on the picosecond to second timescales. The dynamics and electron injection yields were correlated with the PMI energetics and structures. Injection began in less than 1 ps for the dye with the best performance and a significant charge-separated state yield remained at long times. Finally, this chromophore was used to oxidize a covalently bound water oxidation precatalyst following electron injection into TiO2 to demonstrate the utility of the dyes for use in PECs.